Discrimination of ficus deltoidea varieties using HPLC-PDA-TOF-MS / Noraini Kasim … [et al.] - Kasim, Noraini; Afzan, Adlin; Ismail, Nor Hadiani; Vicky Bihud, Nur (Research Innovation Business Unit, 2014)
Numerous Ficus deltoidea products are commercially available as tea or coffee preparation and are gaining increasing popularity in Malaysia. These products are usually formulated from several varieties. Accurate plant identification becomes undeniably important for quality control purposes. Interestingly, classifications of F. deltoidea species based on morphological characteristic remain debatable. In has been reported that two or more varieties may share similar characteristics, with some showing intermediate features. This paper reports preliminary findings in our attempt to establish analytical method to distinguish the varieties using metabolomics platforms. Seven varieties of F. deltoidea which are var. intermedia, var. terengganuensis, var. motleyana, var. deltoidea, var. kunstleri, var. angustifolia and var. bilobata were analyzed using High Performance Liquid Chromatography Photo Diode Array Time of Flight Mass Spectroscopy (HPLC-PDA-TOF-MS) and 600 MHz Nuclear Magnetic Resonance. Our current findings indicate that these varieties differed substantially in terms of their chemical composition.